Drug Therapy for Psychiatric Disorders - Sarkar, S. Siddharth; Sagar, R. Rajesh (Jaypee Brothers Medical Publishers, 2020)
The aim of this book is to focus on the drug therapy for psychiatric disorders. The book Drug Therapy for Psychiatric Disorders was conceived with the intention to provide relevant clinical information to practitioners and students about medications routinely used in the treatment of psychiatric disorders. The book intends to provide focussed material which can be easily assimilated, and the pocketbook format allows bedside use of the book. There are 12 chapters contributed by internationally recognized stalwarts in the field of psychiatry, covering important disorders or specific populations. These include depression, psychotic disorders, anxiety disorders, bipolar disorders, psychosexual disorders, substance use disorders, personality disorders, child and adolescent age group, geriatric age group, pregnant or lactating women, consultation liaison services and psychopharmacology relevant to primary care. The book is envisaged not as a replacement, but as a companion, to other exhaustive texts in the field of psychopharmacology.